THE EVOLUTION OF ELECTORAL JURISPRUDENCE IN COMBATING CANDIDACIES LINKED TO ORGANIZED CRIME: AN ANALYSIS OF TRE-RJ AND TSE DECISIONS ON MILITIAS: An Analysis of TRE-RJ and TSE Decisions on Militias - Souza Rodrigues, Fernando Vinicius; Fernandes Neto, Raimundo Augusto (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
This article analyzes the evolution of Brazilian electoral jurisprudence in combating candidacies linked to criminal organizations, focusing on militias in Rio de Janeiro, specifically in the Baixada Fluminense region. The research employs a qualitative methodology based on documentary analysis of decisions from the Regional Electoral Court of Rio de Janeiro (TRE-RJ) and the Superior Electoral Court (TSE), combined with specialized bibliographic review. The results demonstrate significant jurisprudential evolution in the application of Article 14, §9, and Article 17, §4 of the Federal Constitution, showing a more proactive interpretation in protecting the electoral process. The analysis of precedents reveals a trend toward strengthening preventive control mechanisms for candidacies, prioritizing the protection of election normality and legitimacy. The study concludes that, although there have been significant advances in combating organized crime’s infiltration into the electoral process, challenges persist that require improving legislation and strengthening institutional cooperation between control and oversight bodies.